Financing Innovation Under Ambiguity - Cao, Wenbin; Duan, Xiaoman; Liu, Hening (Journal of Financial and Quantitative Analysis, 2025)
Abstract We develop a real options model in which an entrepreneur facing ambiguity makes optimal investment and financing decisions for an innovation project. We introduce jumps in innovation returns and model investors’ aversion to ambiguity in both diffusion and jump risks. Debt accelerates investment by lowering the threshold and shortening expected waiting time, thereby increasing project value. This effect strengthens under greater ambiguity, offering a novel rationale for why debt—not equity—fosters innovation. Our results provide a coherent explanation for recent empirical findings on debt’s role in innovation and contribute to the broader literature on investment under uncertainty.